Wear And Friction On Gimbal Sealant - Ibrahim, Illuni Islamiah (Universiti Sains Malaysia, 2018)
The natural phenomena of marine ecosystem can cause negative effects to all types of metals especially in term of quality control and reliability of the long-term application product life cycle. Basically, for the gimbal sealant applications focus on stabilizing the product component by reducing the vibration at the component area especially for air and marine transportation. To minimize the vibration effect on the surface of component, the tribology failure analysis in term of wear and friction effect should be identified. Thus, the aim of this project to propose the metal that convenient to applied on the gimbal sealant in marine application. There are several tests must be conducted to measure the behavior of wear and friction effect for different types of metals. The five types of metals were chosen for the testing process that was used as a specimen sample include of pure aluminum (control), aluminum alloy, pure copper, brass alloy and mild steel alloy. The testing process were done by measuring the wear and friction using the pin-on-disc machine (POD), profilometer machine, Vickers hardness testing machine, and universal testing machine (UTM). The tribo-film was analyzed for all types of metals using scanning electron microscopy machine (SEM) to identify wear rate of the surface of the specimen and to identify the element contamination in the surface area by using EDX software. All five types of metals were ranked based on the lowest wear rate and friction to the higher failure effect and it shows that the pure copper is lowest ranked followed by the mild steel alloy and then the aluminum alloy. While, the brass alloy shows the highest ranked for the wear and friction effect and followed by pure aluminum (control) specimen. Thus, the pure copper was chosen as convenient metal to applied on the gimbal sealant in marine application.